2022
DOI: 10.3390/math10081252
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Technology 4.0 Driven Practice on Warehousing Performance: A Hybrid Approach

Abstract: Developing a promising technology that copes with the industrial warehousing environment requires special preparation. It includes infrastructure, equipment, resources, knowledge, efficiencies, and strategies for dealing with failures. This study examines Technology 4.0 driven warehouse practices and performance based on a thorough literature review. The study presents a unique proposition as it considers a two-fold fuzzy Delphi analysis to rank the Technology 4.0 driven practices using best-worst method (BWM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…National and international regulations focus on sustainable operations, energy-efficient processes and low carbon-footprint generation. These objectives could be met by adopting an energy-efficient drone (Awa et al , 2017) that could reduce unnecessary logistics and enhance resource efficiency (Ali and Kaur, 2022). Top management also navigates through all the legal and bureaucratic hurdles for Drone technology inceptions, as these investment-heavy entities are prone to government regulations and zone and area restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…National and international regulations focus on sustainable operations, energy-efficient processes and low carbon-footprint generation. These objectives could be met by adopting an energy-efficient drone (Awa et al , 2017) that could reduce unnecessary logistics and enhance resource efficiency (Ali and Kaur, 2022). Top management also navigates through all the legal and bureaucratic hurdles for Drone technology inceptions, as these investment-heavy entities are prone to government regulations and zone and area restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Green's method was used to ensure that the sample size was adequate (Green 1991). This method requires at least 122 (N > 50 + 8(K) = N > 50 + 8 (9); K is the number of predictor variable) respondents for the further analysis (Ali and Kaur, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Industry 4.0 (I4.0) is known as the fourth industrial revolution, which is the ongoing automation and mechanization of traditional manufacturing processes (Hofmann and Rüsch, 2017; Karnik et al , 2022). It has been reported that Saudi Arabia is still in its infancy in terms of industrialization (Ali and Kaur, 2022), but the market is ready for pioneers to lead the way in the field of I4.0 (Invest Saudi Portal, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With the arrival of the "digital transformation era", e-commerce has been able to develop rapidly, and customers' demands for the efficiency of order item delivery have gradually increased [1]. Warehousing is the key to the efficiency of the supply chain [2], and the order picking operation is the main factor affecting the operational efficiency of warehouse distribution centers [3,4]. Among them, the cost of picking operations accounts for about 55% of the total cost of warehouse operations [5], while the walking time in picking operations accounts for more than 50% of the total operational time [6].…”
Section: Introductionmentioning
confidence: 99%